Analisis Penyimpangan Presuposisi Dalam Komik Strip Pepekomik Edisi Maret-April 2022 - Murod, Yusril Ramli; Herlina, Dewi; Maspuroh, Uah (Peneliti.net, 2024)
This study aims to provide an explanation of the violation of assumptions that have been formed in the reader’s mind and what are the violations of the presuppositions contained in Pepekomik as a comic strip. The data of this research was obtained through listening method, with the advanced technique of speaking free of involvement, note-taking and recording techniques. The data taken focuses on the comic strip of Pepekomik in Facebook and Instagram. The method that is used in this study is a qualitative descriptive method. The type of presupposition that appears most often is lexical presupposition, while the least occurs is existential presupposition. Overall, the presuppositions that appear in the data are used by Pepekomik to violate the assumptions that have been formed in the reader’s mind and by using the violations from the presuppositions to create a twist at the end of the story to bamboozled the reader’s mind. This study can be recommended as a handout in anecdotal text learning because both of them share a common aspect, which is humor conveyed through written texts.